Strategic Study of Good Practice in AR4D partnership - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2015)
This ISPC commented study examines two distinct partnership domains: Multi-stakeholder partnerships (MSPs) in Agricultural Research for Development and Global MSPs approaches. It develops a framework of Partnership and Innovation Modes to assist the CGIAR in embedding its work within the wider archi-tecture of partnership, platforms, and networks that will be required to tackle global scale challenges.